Analisis Hubungan antara Uang Elektronik (E-Money) dan Jumlah Uang Beredar di Indonesia - Narulita, Leira; Setiawati, Ririt Iriani Sri (Jurnal Bisnis Indonesia, 2024)
This study aims to analyze the relationship between electronic money (e-money) and money supply inIndonesia. The data used is electronic money, APMK and the money supply. Using cointegration testanalysis to determine the long-term balance relationship, and granger causality test to determine thereciprocal relationships between variables. The results of the analysis show that the variables ofelectronic money and the money supply have a long-term balance and between electronic moneyvariables and the money supply only have a one-way causality relationship.Keywords: Electronic Money (E-Money); Money Supply; Inflation